The impact of involuntary retirement on senior police officers - Cameron, Trudi M.; Griffiths, Amanda (Oxford University Press, 2017)
There have been no published studies on the impact of involuntary retirement on police officers. This article describes the reported experience of a group of senior police officers who were involuntarily retired from the police service in England and Wales. One-to-one interviews were conducted 2–15 months after retirement with nine former Superintendents and Chief Superintendents aged 48–56 years old, with an average of 30 years of service. Interviews were recorded, transcribed, and subject to thematic analysis. Three overarching themes emerged: perceived breach of a psychological contract, impact on individuals and families, and life ‘after the job’. Positive outcomes included having increased time for fitness and leisure activities, and entering new careers. Negative outcomes included inadequate time to prepare for retirement, financial challenges, difficulties navigating the civilian job market, low mood, and feelings of isolation and abandonment. Implications for the future management of involuntary retirement are presented.